Організація роботи зі службовими документами в органах державної влади Чернігівської губернії в першій половині ХІХ ст. - Леміш, Н. (Архіви України, 2008)
Based on the case of Chernihiv Provincial Board and the Chancellery of Chernihiv civil Governor, the author conducts an analysis of records management at principal provincial administrative bodies during the first half of XIX century; its structure and development in the framework of public administration reforms.